Combined Pharmacological and surgical treatments for recurrent chemical peritonitis due to rupture of a bilateral mature cystic teratoma: a case report - Sho Kudo; Hideaki Tsuyoshi; Kino Tsuji; Yoshiaki Tanaka; Makoto Orisaka; Yoshio Yoshida (BMC Women's Health)
Abstract Background Mature cystic teratomas, a common type of benign ovarian tumors, are associated with complications such as twisting and tumor rupture; Rupture can cause severe chemical peritonitis, and no management policy has been established for the intraoperative and postoperative periods. Although peritoneal lavage and reoperation have been reported, the optimal treatment approach remains undetermined. Case presentation A 30-year-old woman (gravida 0, para 0, and no sexual history) presented with abdominal pain and fever. Blood examination revealed high levels of WBC 9200/µL and CRP 23.7 mg/dL, although hemoglobin was normal. Serum tumor marker levels were also elevated (CA125 58.5 U/mL, CA19-9 36117 U/mL). Abdominal computed tomography revealed bilateral ovarian tumors (92 and 68 mm in the right and left ovaries, respectively). Each tumor cavity had calcification with increased fatty tissue density. We performed laparoscopic surgery for suspected diagnosis of torsion or rupture of a mature cystic teratoma. Intraoperative findings showed spontaneous rupture followed by chemical peritonitis. Therefore, we performed removal of the bilateral adnexal tumors and peritoneal lavage with 3000 mL warm saline to remove fatty components from the abdominal cavity. We also inserted an intra-abdominal drain to remove the residual fatty components. Amoxicillin was also administered for 10 days after surgery. The inflammatory response decreased, and the fever diminished 1 day postoperatively. The patient was discharged on the 10th postoperative day. However, on the 20th postoperative day, the fever and abdominal pain recurred. WBC 16,700/µL, CRP 26.46 mg/dL and tumor marker (CA125 172.3 U/mL, CA19-9 225.2 U/mL) levels were high. Intravenous administration of Prophylactic antibiotics was initiated. As no bacteria were detected in the blood cultures, we started oral prednisolone (5 mg/day) to treat the recurrent chemical peritonitis-induced inflammation. The blood test results and symptoms gradually improved. The patient was discharged on the 37th postoperative day. Conclusion To date, no systematic review has focused on determining the treatment strategy for bilateral rupture of mature cystic teratomas and severe refractory chemical peritonitis. Treating the patient with laparoscopic surgery at the first occurrence and oral steroids for peritonitis recurrence can help avoid highly invasive treatments, such as reoperation or laparotomy.